Mobilités sociales et spatiales d’Africain·es-Américain·es vers la banlieue de « l’entre-deux » dans la deuxième moitié du 20ème siècle : le cas d’Euclid, Ohio - Marion MARCHET (E-REA)
Through the case study of Euclid, an inner-ring and formerly industrial suburb of Cleveland, Ohio, this paper focuses on patterns of African American suburbanization into spaces of “in-betweenness” of Midwestern suburbia. At first largely understudied at the expense of more traditional and affluent suburban spaces, yet under closer scrutiny since the 2014 Black Lives Matter uprising in Ferguson, Missouri, these suburban spaces became in the last quarter of the 20th century privileged sites for a more fragile yet mobile section of the “New Black Middle Class.” Through archival work and oral history interviews, this article seeks to document their upward-mobile journeys that began in the course of the 1970s from the center of Cleveland, sometimes elsewhere, and into Euclid. It will attempt to demonstrate more precisely the extent to which, before becoming powerful barometers of the state of racial relations in the twenty-first century United States, these suburban spaces carried at first many of the dreams and ambitions of an intermediary segment of the African American population claiming its share of material comfort and security in the post-Civil Rights era.